HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN KONDISI KESEHATAN RONGGA MULUT PENDERITA DIABETES MELLITUS TIPE 2 (Studi Terhadap Pasien RSI Sultan Agung Semarang Tahun 2012) - Rezky Hidayati; Uswatun N.A Darjono; Rochman Mujayanto; Diyah Fatmasari (Jurnal Medali, 2013)
Type 2 diabetes mellitus patients are individuals who are potentially exposed to infectious diseases due to their weakened immune. One of these infections is in the oral cavity. Diabetes mellitus also affects the patientâ€™s psychological condition, such as anxiety and depression. The aim of the study is to determine the relationship between levels of anxiety with oral health of diabetes mellitus patients type 2 RSI Sultan Agung Semarang in 2012.This research was used analytic observational on cross sectional design, conducted on 30 patients at the RSI Sultan Agung Semarang in 2012 with the simple random sampling technique. Anxiety levels of patients was measured by using questioner of Hammilton Anxiety Rating Scale (HAM-A). Caries status was measured by the DMF-T index, periodontal tissue status was measured by russel periodontal index, status saliva was measured by salivary status sialometri technique. The results were analyzed with the product moment pearson correlation.From the result showed that there was a significant relationship between the level of anxiety with dental caries status (p = 0.004), anxiety levels with periodontal tissue status (p = 0.000), and anxiety levels with saliva status (p = 0.009).Based on the research it can be inferred that there was a significant relationship between the level of anxiety with oral health of diabetes mellitus type 2 patients at RSI Sultan Agung Semarang in 2012.Â Keywords: Anxiety, oral health, diabetes mellitus type 2